A Comparison of Computational Methodologies for the Structural Modelling of Biologically Relevant Zinc Complexes - Mera-Adasme, R; Borges-Martinez, M (Springer Verlag, 2019)
The impact of a variety of modern computational methods on the structure of biologically relevant zinc complexes is studied. Different density functionals and a Hartree-Fock-based method, scalar-relativistic effects, and basis set integration grid choices, among others, are assessed for set of high-resolution crystallographic structures. While a previous study recommends incorporating relativistic effects into density functional theory calculations in order to improve the accuracy of obtained geometries for small Zn(II) coordination compounds, we show that, for the set in study, relativistic effects do not affect the geometries to a significant extent. The PBEh-3c composite method emerges as good alternative for the treatment of Zn(II) complexes, while the HF-3c method can be employed when computational efficiency is important. [Figure not available: see fulltext.]. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.